Effleurage Massage for Pain Relief in Pregnant Women - Mutia Nadra Maulida (Conferences of Medical Sciences Dies Natalis, 2020)
Pregnancy is an event that begins with conception and ends with the onset of labor. Pregnancy is divided into three trimesters, the first trimester (0-12 weeks), the second trimester (13-27 weeks), and the third trimester (28-40 weeks). During the pregnancy process will cause various changes in all body systems, both physiological changes and psychological changes that can cause discomfort to pregnant women. Physiological changes that often occur in pregnant women such as dyspnea, insomnia, gingivitis, frequent urination, pressure and discomfort in the perineum, back pain, constipation, varicose veins, fatigue, Braxton hicks contractions, leg cramps, ankle edema. Not only physiologically, changes in pregnant women also occur psychologically such as changes in mood and increased anxiety.One of the physiological changes that pregnant women often complain about is back pain. According to Ratih (2016), the results of research on pregnant women in various regions of Indonesia reached 60-80% of people who experience back pain in their pregnancy. The reported prevalence of back pain in pregnancy varies from 50% in the UK and Scandinavia to 70% in Australia. Back pain experienced by pregnant women will peak at week 24 to week 28, just before abdominal growth reaches its maximum point. Most back pain during pregnancy occurs due to changes in the spinal muscles, as much as 70%.Back pain in pregnant women can be treated both pharmacologically and non pharmacologically. One of the non-pharmacological therapies that can be given is Effleurage Massage, which provides a gentle, slow and uninterrupted massage on the back of pregnant women so that it can cause relaxation and reduce pain.